Evaluation of SDE, SFE and SPME/GC-MS for extraction and determination of aroma compounds from Vilcabamba - Ecuadorian roasted coffee [Evaluación de DES, FSCY SPME/CG-MS para la extracción y determinación de compuestos responsables del aroma de café tostado de Vilcabamba - Ecuador] - Figueroa Hurtado, J. (2016)
The aim of this study was to compare the usefulness of three extraction methods: solid-phase microextraction (SPME) with four different coating (PDMS, PDMS/DVB, DVB/CAR/PDMS and PA), supercritical fluid extraction with carbon dioxide (SCF) and simultaneous distillation and extraction (SDE) for isolation of flavor compounds from roasted ground coffee (Coffea arabica L. var. Typica) of Vilcabamba (Ecuador). Identification and characterization of volatile compounds were achieved using gas chromatography / mass spectrometry (GC-MS). Analysis of variance and principal components analysis was done. For the SPME method the coating material affect the amount and concentration of compounds extracted, the DVB/CAR/PDMS coating provided the most representative aroma extract (44 compounds were identified). The SCF method allowed extracting a higher amount of compounds and also their identification by GC-MS (72) that SDE (64) and SPME (57), in addition provide higher extractions. The acetic acid, caffeine, furfuryl alcohol, furfural, 5-methylfurfural, butylated hydroxytoluene and maltol were the compounds with higher concentrations found with SPME and SDE, with SCF were found higher concentration to compounds with high molecular weights (> 194 g/mol). Preferably SPME-DVB/CAR/PDMS method should be used for a characterization of coffee aroma compounds.